Implementation Of Online Single Submissionin The Issuance Of Microand Small Business Lincenses (Iumk) At The One-Stop Integrated Services Agency Of Denpasar City - Desak Made Mettayuni; Ida Ayu Putu Sri Widnyani; I Made Sumada (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
The Denpasar City Investment and One-Stop Integrated Services Service (DPMPTSP) has utilized information technology by implementing Electronically Integrated Business Licensing or Online Single Submission (OSS). OSS is a business licensing system issued electronically by the OSS institution on behalf of the minister, head of the institution, governor or regent/mayor to business actors. The aim is to reduce bureaucracy and speed up the business licensing process which was previously complicated and took a lot of time. However, the implementation of OSS in issuing Micro and Small Business Permits (IUMK) in Denpasar City is not yet optimal because some business actors still do not understand the system. This research uses a qualitative approach to understand more deeply the phenomena related to fees in the licensing process. Carried out at the Denpasar City DPMPTSP Office because Denpasar City has implemented E-Government and is the capital of Bali Province. Government Regulation Number 24 of 2018 concerning OSS is the legal basis for implementing electronically integrated business licensing for IUMK